Ancillary and instrumental body movements during inhalation in clarinetists - Nusseck, Manfred; Immerz, Anna; Hohagen, Jesper; Spahn, Claudia (Frontiers in Psychology, 2024)
Playing a musical instrument requires physical movements that are involved in sound production and movements with more expressive and communicative characteristics. Both movements occur simultaneously during a performance; however, the interaction between them is still unclear. By using motion capture technology, movement patterns of clarinetists were analyzed at certain points in a performance to investigate how instrumental and ancillary movements interplay. With motion capture, movements in the arms and knees of clarinetists during a performance were recorded. Mean angular movements at specific points in the piece, where some players inhaled and others did not, were compared. While the players who inhaled adopted significantly more upright body and neutral arm positions, the players who did not inhale seemed less interrupted in their performance. The results showed that the players performed rather individual ancillary movements, but at specific points, such as a melodic transition, they performed similarly. At points in the melody at which some players needed to inhale, others prepared their playing according to the inhalation moment to adopt a suitable body position. The ancillary movement was therefore interrupted by the physiological necessity to inhale. The findings provide more insights in the interplay of instrumental and ancillary movements during a performance.